Citizen Participation after the Fall of Communism in Romania: Evolving Perceptions and Practices in Local Decision-Making and Governance - Bianca Veronica Radu; Cristina Haruța (Transylvanian Review of Administrative Sciences, 2025)
The paper examines the perceptions of Romanian local public institutions’ representatives regarding citizen participation in the decision-making process in Romania. We examined the decade-long changes regarding citizen participation in the decision-making process in Romania. To this end, we conducted a survey in late winter 2009 and early spring 2010 on a representative sample of City Halls and County Councils in Romania, collecting 381 valid surveys. We replicated the same survey from March 2024 until July 2024 and collected responses from 621 institutions. The research revealed moderate development in local government toward a more participatory culture, involving citizens more actively in the decision-making process in Romania. However, this progress is not evenly distributed across the local public administration, and the degree of citizen participation appears to be influenced by the size of the local communities. The larger the size of local communities, the higher the degree of citizens’ involvement in the decision-making process is.